Accelerationism: a timely provocation for the critical sociology of education. Issue 1 (2nd January 2017) - Sellar, Sam; Cole, David R.
Abstract: Accelerationism is a theoretical movement that seeks to mobilise reason and technological development as a strategy for moving beyond capitalism. The first wave of accelerationism took the effects of capitalism at their most pernicious and suggested that they have not gone far enough. More recent work has complicated this project and explored political, epistemic and aesthetic accelerations. The central push to accelerate, and therefore to manifestly alter time, has consequences in terms of how one understands temporality in education. This article outlines the development of accelerationism and examines whether this theoretical movement can aid critical analysis of the growing presence in education of commercial technology providers, new modes of data analytics, and the application of machine learning algorithms to analyse data. These developments provide a useful example in relation to which a critical question can be asked: is it possible to accelerate technological development in education separate from its capitalist development?